IL-6 is involved in malignancy and doxorubicin sensitivity of renal carcinoma cells. Issue 1 (2nd January 2018) - Chen, Yanqiang; Liu, Jianzhen; Lv, Pei; Gao, Jiangyan; Wang, Mingzheng; Wang, Yongjun
ABSTRACT: Various survival factors such as the pleiotropic cytokine interleukin-6 (IL-6), a major mediator of inflammation and activator of signal transducer and activator of transcription 3 (STAT3), serve to block apoptosis in cancer cells. Our present study revealed that the expression of IL-6, while not other IL-2, IL-4, IL-8, or IL-10, was significantly elevated in resistance of renal carcinoma cells (RCC) when compared with human renal proximal tubule epithelial cell line HK-2. The inhibition of IL-6 by siRNA can suppress the proliferation, migration and invasion of RCC cells and increase the doxorubicin (Dox) sensitivity. While recombination IL-6 can attenuate the inhibition effects of Dox on proliferation of RCC cells. Further studies indicated that inhibition of IL-6 by siRNA can decrease the phosphorylation of STAT3 in RCC cells. Over expression of STAT3 increased the proliferation, migration and invasion of RCC cells and reversed si-IL-6 induced increase of Dox sensitivity of ACHN and A498 cells. In addition, IL-6 treatment can activate ERK1/2 via increasing its phosphorylation. PD98059, the ERK1/2 inhibitor, attenuated IL-6 induced proliferation and synergistically increased the Dox sensitivity of si-IL-6 transfected ACHN cells. Collectively, our data suggested that IL-6 plays an important role in malignancy and Dox sensitivity of RCC. The targeted inhibition of IL-6 signals might be a promising therapeutic strategy for the treatment of renal cancer.